Sea Urchin - From Environment to Aquaculture and Biomedicine 2017
DOI: 10.5772/intechopen.70301
|View full text |Cite
|
Sign up to set email alerts
|

The Sea Urchin Embryo: A Model for Studying Molecular Mechanisms Involved in Human Diseases and for Testing Bioactive Compounds

Abstract: Most of the current knowledge concerning fundamental genetic mechanisms, evolutionary processes and development, cellular physiology, and pathogenesis comes from studies of different animal model systems. Whereas mice, rats, and other small mammals are generally thought of as the typical model systems used by researchers in biomedical studies, aquatic models including both freshwater and marine organisms have long proved to be essential for the study of basic biological processes. For over a century, biologist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 141 publications
0
15
0
Order By: Relevance
“…Detailed SAR examination of these compounds suggested that the observed MOLT-4 effect is likely a result of their interaction with the same cellular target(s) and/or molecular networks in both assay systems. This assumption is supported by the fact that numerous regulatory networks and signaling pathways common for other animals and humans were first described and investigated comprehensively in the sea urchin embryos. Importantly, sea urchin and human genomes share more than 7000 genes . Subsequent studies of possible mechanisms that could mediate MOLT-4 specificity allowed us to eliminate Notch, Wnt/β-catenin, receptor tyrosine kinases (VEGF/VEGFR, FGF/FGFR), PI3K, and Raf-MEK-ERK signaling pathways as possible targets of BIPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed SAR examination of these compounds suggested that the observed MOLT-4 effect is likely a result of their interaction with the same cellular target(s) and/or molecular networks in both assay systems. This assumption is supported by the fact that numerous regulatory networks and signaling pathways common for other animals and humans were first described and investigated comprehensively in the sea urchin embryos. Importantly, sea urchin and human genomes share more than 7000 genes . Subsequent studies of possible mechanisms that could mediate MOLT-4 specificity allowed us to eliminate Notch, Wnt/β-catenin, receptor tyrosine kinases (VEGF/VEGFR, FGF/FGFR), PI3K, and Raf-MEK-ERK signaling pathways as possible targets of BIPP.…”
Section: Discussionmentioning
confidence: 99%
“…40−43 Importantly, sea urchin and human genomes share more than 7000 genes. 44 Subsequent studies of possible mechanisms that could mediate MOLT-4 specificity allowed us to eliminate Notch, Wnt/βcatenin, receptor tyrosine kinases (VEGF/VEGFR, FGF/ FGFR), PI3K, and Raf-MEK-ERK signaling pathways as possible targets of BIPP. Although MMP-9/hatching enzyme was identified as one of the possible BIPP 11 targets, specific cytotoxicity against MOLT-4 cells was unrelated to this mode of action.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The sea urchin (Echinodermata: Echinoidea) embryo has long been used as a model organism for biological developmental studies [ 26 , 27 , 28 , 29 ]. Several factors make this system suitable for conducting a wide range of biological tests.…”
Section: The Sea Urchin Embryomentioning
confidence: 99%
“…Furthermore, as invertebrate species, sea urchins are not subject to animal welfare concerns. This trait satisfies the strategy for developing alternative approaches to the use of vertebrates in biological testing [ 27 ].…”
Section: The Sea Urchin Embryomentioning
confidence: 99%
See 1 more Smart Citation